How can cerebral edema during treatment of diabetic ketoacidosis be avoided?. Issue 4 (June 2014) - Watts, Wendy; Edge, Julie A
<x xml:space="preserve">Abstract</x> Cerebral edema during diabetic ketoacidosis (DKA) is a rare complication but it can be devastating, with significant mortality and long‐term morbidity. Certain risk factors have been teased out with some large case–control studies, but more research needs to be done to make management guidelines safer. This article will discuss how DKA might be prevented from occurring in the first instance, known risk factors for cerebral edema, fluid and insulin management, the importance of careful monitoring during DKA treatment, and the importance of recognizing and acting on the earliest symptoms to prevent long‐term harm.